Network Effects, Ethnic Capital and Immigrants' Earnings Assimilation: Evidence from a Spatial, Hausman-Taylor Estimation - Sholeh A. Maani; Xingang Wang; Alan Rogers (Institute for the Study of Labor (IZA), 2015)
Do ethnic enclaves assist or hinder immigrants in their economic integration? In this paper we examine the effect of ethnic capital (e.g. ethnic network and ethnic concentration) on immigrants earnings assimilation. We adopt a spatial autoregressive network approach to construct a dynamic network variable from micropanel- data to capture the effects of spatial-ethnic-specific resource networks for immigrants. The spatial lag structure is combined with a Hausman-Taylor (1981) panel data model. The HT estimator adopts the features of both a fixed-effects and randomeffects model that utilizes the added information in the panel setting, as well as instrumental variables (IV) estimation, controlling for endogeneity of the spatial lag variable and other endogenous explanatory variables (Baltagi, 2013). We also show that the spatial structure is identified in this Hausman-Taylor setting. We examine the effects of ethnic capital and human capital using an eight-year Australian panel data set (HILDA). Results show that immigrants labor market integration is significantly affected by the local concentration and resources of their ethnic group.
Keywords: J30; J31; Z13; Z18; 330; ethnic concentration; ethnic network; ethnic capital; assimilation; spatial autoregressive lag model; panel data